Uptake, Internalization and Degradation of the Novel Plasminogen Activator Reteplase (BM 06.022) in the Rat - Kuiper, J; van de Bilt, H; Martin, U; van Berkel, Th J C (Thrombosis and Haemostasis, 1995)
The catabolism of the novel plasminogen activator reteplase (BM 06.022) was described. For this purpose BM 06.022 was radiolabelled with l25I or with the accumulating label l25I-tyramine cellobiose (l25I-TC).BM 06.022 was injected at a pharmacological dose of 380 μg/kg b.w. and it was cleared from the plasma in a biphasic manner with a half-life of about 1 min in the α-phase and t1/2of 20-28 min in the β-phase. 28% and 72% of the injected dose was cleared in the α-phase and β-phase, respectively. Initially liver, kidneys, skin, bones, lungs, spleen, and muscles contributed mainly to the plasma clearance. Only liver and the kidneys, however, were responsible for the uptake and subsequent degradation of BM 06.022 and contributed for 75% to the catabolism of BM 06.022. BM 06.022 was degraded in the lysosomal compartment of both organs. Parenchymal liver cells were responsible for 70% of the liver uptake of BM 06.022. BM 06.022 associated rapidly to isolated rat parenchymal liver cells and was subsequently degraded in the lysosomal compartment of these cells. BM 06.022 bound with low-affinity to the parenchymal liver cells (550 nM) and the binding of BM 06.022 could be displaced by t-PA (IC50 5.6 nM), indicating that the low-density lipoprotein receptor-related protein (LRP) could be involved in the binding of BM 06.022. GST-RAP, which is an inhibitor of LRP, could in vivo significantly inhibit the uptake of BM 06.022 in the liver.It is concluded that BM 06.022 is metabolized primarily in the liver and the kidneys. These organs take up and degrade BM 06.022 in the lysosomes. The uptake mechanism of BM 06.022 in the kidneys is unknown, while LRP is responsible for a low-affinity binding and uptake of BM 06.022 in parenchymal liver cells.